Method for Determining the Level of Centralization in BTC Lightning Nodes: A Centrality Analysis of the Lightning Network - Atmanavičiūtė, Laura; Vanagas, Tomas; Masteika, Saulius (Vilnius University Open Series, 2024)
This study explores the Bitcoin Lightning Network (BLN), a Layer 2 solution for faster and cheaper transactions. Concerns about centralization have emerged due to the increasing concentration of power among specific nodes, named “hubs.” Statistical measures like the Gini coefficient reveal a trend towards centralization, challenging the LN’s decentralized nature. Consequently, further research is necessary to address this issue and ensure the integrity of the LN architecture. This paper aims to establish a method for determining the level of centralization within the BLN by applying centrality analysis techniques. Study revealed that over the six-year period Gini coefficient increased from 0.87 to 0.955, indicating significant inequality and apparent centralization of BLN nodes.
Keywords: Bitcoin; Lightning Network; Centralization; Data processing